Misexpression of Pknox2 in Mouse Limb Bud Mesenchyme Perturbs Zeugopod Development and Deltoid Crest Formation - Zhou, Wenrong (Public Library of Science, 2013)
The TALE (Three Amino acid Loop Extension) family consisting of Meis, Pbx and Pknox proteins is a group of transcriptional co-factors with atypical homeodomains that play pivotal roles in limb development. Compared to the in-depth investigations of Meis and Pbx protein functions, the role of Pknox2 in limb development remains unclear. Here, we showed that Pknox2 was mainly expressed in the zeugopod domain of the murine limb at E10.5 and E11.5. Misexpression of Pknox2 in the limb bud mesenchyme of transgenic mice led to deformities in the zeugopod and forelimb stylopod deltoid crest, but left the autopod and other stylopod skeletons largely intact. These malformations in zeugopod skeletons were recapitulated in mice overexpressing Pknox2 in osteochondroprogenitor cells. Molecular and cellular analyses indicated that the misexpression of Pknox2 in limb bud mesenchyme perturbed the Hox10-11 gene expression profiles, decreased Col2 expression and Bmp/Smad signaling activity in the limb. These results indicated that Pknox2 misexpression affected mesenchymal condensation and early chondrogenic differentiation in the zeugopod skeletons of transgenic embryos, suggesting Pknox2 as a potential regulator of zeugopod and deltoid crest formation.